2006
DOI: 10.1177/0269881106068825
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of synaptic protein mRNAs in STOP (MAP6) mutant mice

Abstract: proteins, was quantified in female STOP null (n=7), heterozygous (n=5) and wild type (n=6) mice. For STOP null and heterozygous mice, synaptophysin, VGlut1, GAP-43 and spinophilin mRNAs were decreased in the hippocampus, whilst in addition in the null mice, synaptophysin, VGlut1 and spinophilin mRNAs were decreased in the cerebellum. Alterations in synaptic protein mRNA expression were also detected in the frontal and occipital cortex.MAP2 mRNA expression was unchanged in all brain regions. The profile of mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 90 publications
0
33
0
Order By: Relevance
“…The Map6 gene product known as STOP (stable tubule only peptide) is a Ca 2 + -calmodulin regulated microtubule-associated protein present in neurons, oligodendrocytes, and astrocytes (Bosc et al, 2003;Denarier et al, 1998;Galiano et al, 2004). Mice lacking a functional copy of STOP (STOP null) display several synaptic abnormalities that are accompanied by an array of cognitive deficits (Begou et al, 2008;Brun et al, 2005;Eastwood et al, 2007;Powell et al, 2007). STOP null mice display a two-fold reduction in pre-synaptic glutamatergic vesicle density in the CA1 region of the hippocampus, a brain structure implicated in learning and memory (Andrieux et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Map6 gene product known as STOP (stable tubule only peptide) is a Ca 2 + -calmodulin regulated microtubule-associated protein present in neurons, oligodendrocytes, and astrocytes (Bosc et al, 2003;Denarier et al, 1998;Galiano et al, 2004). Mice lacking a functional copy of STOP (STOP null) display several synaptic abnormalities that are accompanied by an array of cognitive deficits (Begou et al, 2008;Brun et al, 2005;Eastwood et al, 2007;Powell et al, 2007). STOP null mice display a two-fold reduction in pre-synaptic glutamatergic vesicle density in the CA1 region of the hippocampus, a brain structure implicated in learning and memory (Andrieux et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, STOP null mice exhibit both short-and long-term synaptic plasticity defects in the hippocampus (Andrieux et al 2002) associated with depleted glutamatergic vesicle pools. Moreover, levels of mRNAs encoding synaptic proteins, such as synaptophysin, growth-associated protein-43, and spinophilin, are decreased in specific hippocampic subregions (Eastwood et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Synaptophysin is a marker for synapses and synaptic strength, and has been used for the quantification of synapses (Calhoun et al, 1996). On the other hand, GAP-43 is an important mediator of neurite outgrowth (Jap Tjoen San et al, 1991), neuronal regeneration (Meiri et al, 1988) and a marker of the presynaptic terminals (Eastwood et al, 2007). Consistent with the findings in this study, it has recently been shown that CIH exposure reduces afferent neurotransmission in the intermediate and caudal NTS (Almado et al, 2012).…”
Section: Discussionmentioning
confidence: 99%